Modelling the age-related decline in cross-country ski performance - Heil, D. P. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: While aerobic capacity tends to decline after the age of 30-35 years of age, endurance performance ability can remain elevated well into an athlete's 40's for high-skill requiring sports such as cross-country skiing. The present study investigated the use of a regression modelling technique to describe the age-related declines in ski performance, as well as for adjusting cross-country ski race times for the overall age-related decline in race performance.